If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-12=a-2
We move all terms to the left:
-12-(a-2)=0
We get rid of parentheses
-a+2-12=0
We add all the numbers together, and all the variables
-1a-10=0
We move all terms containing a to the left, all other terms to the right
-a=10
a=10/-1
a=-10
| j/6+41=45 | | 96=8(n+1) | | 2h+4-55=-3h+4 | | 5x+14=109 | | Y=117.8+-1.4x | | 16=-2h | | 5(3v-4)=40+3v | | 1/2(x+12=4x-1 | | 4=y-77/5 | | 3+14y-1=8y+52-4y | | 25d+5=80 | | 12=2+y | | 0.25x=5+5 | | y/2-10=28 | | P=129p=108 | | 5k-10÷2=-7 | | y-(-10)=-6 | | 14u=60 | | 6(^x+2)=12 | | 9+3y-4=7y+5-3y | | (7-v)(5v-8)=0 | | 11r+-77=-88 | | 9+3y-4=7y+5-37 | | -12s=-60 | | 10=-7x+6x+4 | | 11r+44=-8 | | 7x+1+6x-6=55 | | 5x0-2=8 | | 1/3m=-6 | | 8x-60=3x+12 | | 293x+10=x+22 | | 93^x−10=(1/81)^1/6 |